Regional Financial Transparency Towards Independence of Development and Good Governance - Suryana, Eka Pala; Akla, Miftahul (Universitas Negeri Semarang, 2020)
The development of technology makes the era of information openness become one of crucial issues, especially in modern technology and globalization. The modernization and globalization also affected to government management which the e-government system is one of the obligatory things. This research analyzed and describe a comprehensive picture concerning to transparency in regional financial sectors. This research tried to seek how the implementation of regional financial transparency can support the concept of good governance in Indonesia. The research emphasized that on implementing the financial transparency, the community roles have a strategic position, as well as for NGOs and community groups. They directly affected to the successful of financial transparency in regional.